Control of a charging station for electric vehicles (2020)
A weighted average current control applied to a three-phase inductor-capacitor-inductor grid-connected battery charger for electric vehicles is presented in this paper. The proposed controller is based on a combination of the partial currents of the system (inverter and grid currents), which are feedback into the control loop. Therefore, by using this approach a reduction of the system order is achieved. The proposed controller allows a bidirectional control of the converter currents, thus allowing both, a controlled charge of the battery and the injection of the current with low distortion in the grid. Further, the implemented controller does not needs to measure the inverter currents. The control strategy is validated with simulation results. © Published under licence by IOP Publishing Ltd.